Trial marketing in the Pan-Canadian Early Detection of Lung Cancer Study. (April 2020) - Rudkowski, Janice L; Pond, Gregory R; Tremblay, Alain; Johnston, Michael; Goss, Glen; Nicholas, Garth; Martel, Simon; Bhatia, Rick; Liu, Geoffrey; Schmidt, Heidi; Tammemagi, Martin C; Atkar-Khattra, Sukhinder; et al.
Background: Recruitment to clinical trials is suboptimal, increasing costs, and delaying the potential implementation of clinical advances. Among other barriers, the lack of marketing experience among trialists may limit recruitment. In this observational study, in the context of the Pan-Canadian Early Detection of Lung Cancer Trial, we assessed the value of a motivational survey of study participants in planning a tailored advertising campaign and analysed the value of individual components of advertising in generating telephone calls to the study and recruited subjects. Methods: The Pan-Canadian Early Detection of Lung Cancer Trial was a single arm study assessing risk modelling for lung cancer screening by low-dose computed tomography scan and autofluorescence bronchoscopy. Individuals were recruited to eight sites across Canada without a central marketing plan. On contact with the study, individuals reported how they heard about the study according to a predefined list. One site, the Juravinski Cancer Centre, worked with a marketing expert to develop a survey to assess participant motivations, source of study awareness, and personal habits. The survey was used to develop a media campaign for recruitment. Media events were collected from all sites. The primary analysis assessed the number of telephone contacts and recruited subjects associated with various media factors. Individual print media characteristics were assessed for their effect on recruitment. Results: At all sites, 7059 individuals contacted the study, and 2537 were eligible and recruited. Among 52 individuals completing the Juravinski Cancer Centre survey, motivation included concern for personal risk of lung cancer (71%), followed by desire to contribute to a cure (67%), followed by personal knowledge of a person with lung cancer (50%). Most reported hearing of the study from the newspaper (58%) despite no print ad yet being distributed. With survey input, a newsprint campaign was executed. The number of media events varied by site (median: 13, range: 3–28). Among all recruits, 56.4% reported referral by newspaper followed by family/friend (14%). Telephone contacts and recruited subjects per event varied significantly by site, while unpaid media events appeared superior to paid events. Print media characteristics associated with increased telephone contacts and recruitment included use of a rational appeal (vs a mixed rational–emotional), less use of white space, and larger headline font. Conclusion: A survey of trial candidates provides useful information regarding personal motivation, media use, and lifestyle. Unpaid media events appear superior in generating recruitment, while print media may be superior to radio and television in selecting eligible recruits. The utility of individual print media characteristics appears to differ from the commercial advertising literature. Further research on marketing in clinical trials is encouraged to improve recruitment (ClinicalTrials.gov registration: NCT00751660, https://clinicaltrials.gov/ct2/show/NCT00751660 ).